2018
DOI: 10.3390/ijerph15020300
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Exploration of the Effects of Exposure to Images of Nature on Rumination

Abstract: Exposure to natural environments has been shown to have beneficial effects on mood. Rumination is a thinking style associated with negative mood, and sometimes depression, and is characterized by repetitive, intrusive thoughts, often with a negative emotional element. This study investigated whether exposure to nature, operationalized using photographs presented as a slideshow, could aid reduction in levels of state rumination. An experimental, within-between (Time x Condition) participant design was used; par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
2
17
0
Order By: Relevance
“…Specifically speaking, under a high level of rumination, negative life events were more likely to accelerate the emergence of suicidal ideation in college students, which was consistent with the existing research [49]. Evidence suggests that the main characteristics of rumination are repetitive and intrusive thoughts [50], and rumination can lead to depression and extreme anxiety [51]. Confronted with negative life events, college students may lapse into brooding about their impact and the associated negative emotions.…”
Section: Discussionsupporting
confidence: 80%
“…Specifically speaking, under a high level of rumination, negative life events were more likely to accelerate the emergence of suicidal ideation in college students, which was consistent with the existing research [49]. Evidence suggests that the main characteristics of rumination are repetitive and intrusive thoughts [50], and rumination can lead to depression and extreme anxiety [51]. Confronted with negative life events, college students may lapse into brooding about their impact and the associated negative emotions.…”
Section: Discussionsupporting
confidence: 80%
“…Simulated nature might primarily benefit negative affect because previous research (Lohr and Pearson-Mims, 2000;van den Berg et al, 2003) and attention restoration theory (Kaplan, 1995) suggest that if people feel like they are away from their everyday demands through visual access to nature, these feelings can interrupt cognitive demands and maladaptive patterns of thought. Such demands and patterns manifest themselves in reductions of negative affect but not necessarily increases in positive affect (Golding et al, 2018). We found that positive affect was greater in the VR condition than in the control condition.…”
Section: Discussionmentioning
confidence: 61%
“…A growing literature has produced an evidence base suggesting that nature exposure helps to deliver mental health benefits [ 7 ], reduced stress levels [ 8 ], less rumination (i.e. the dwelling on negative aspects of a recent situation) [ 9 ], and increased overall sense of wellbeing [ 10 ]. Not only does outdoor recreation and exercise have a positive impact on mental health, but physical health as well.…”
Section: Introductionmentioning
confidence: 99%